2014
DOI: 10.1016/j.stemcr.2013.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Supplementation Reduces Genomic Aberrations in Human Induced Pluripotent Stem Cells

Abstract: SummarySomatic cells can be reprogrammed to induced pluripotent stem cells (iPSCs) using oncogenic transcription factors. However, this method leads to genetic aberrations in iPSCs via unknown mechanisms, which may limit their clinical use. Here, we demonstrate that the supplementation of growth media with antioxidants reduces the genome instability of cells transduced with the reprogramming factors. Antioxidant supplementation did not affect transgene expression level or silencing kinetics. Importantly, iPSCs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
77
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 76 publications
(83 citation statements)
references
References 28 publications
6
77
0
Order By: Relevance
“…Moreover, new methods of small molecule-mediated iPSC generation have been shown to modulate the transition to aerobic glycolysis (Zhu et al, 2010). Although the precise effect of ROS on signaling pathways during the reprogramming process has not been evaluated, levels of ROS appear to increase during reprogramming and to cause damage to DNA, which can be minimized by the addition of NAC (Ji et al, 2014). The efficiency of reprogramming and continued maintenance of iPSCs can also be improved under low O 2 conditions (Ezashi et al, 2005).…”
Section: Ros As a Mediator Of Stem Cell Fate And Reprogrammingmentioning
confidence: 99%
“…Moreover, new methods of small molecule-mediated iPSC generation have been shown to modulate the transition to aerobic glycolysis (Zhu et al, 2010). Although the precise effect of ROS on signaling pathways during the reprogramming process has not been evaluated, levels of ROS appear to increase during reprogramming and to cause damage to DNA, which can be minimized by the addition of NAC (Ji et al, 2014). The efficiency of reprogramming and continued maintenance of iPSCs can also be improved under low O 2 conditions (Ezashi et al, 2005).…”
Section: Ros As a Mediator Of Stem Cell Fate And Reprogrammingmentioning
confidence: 99%
“…Some of the recent studies have sought to address nutritional requirements for pluripotency reprogramming and determined that some common dietary supplements have noteworthy potential for improving reprogramming efficiency and iPSC quality (Table , Fig. ).…”
Section: Nutritional Supplements For Pluripotency Reprogrammingmentioning
confidence: 99%
“…Relatively higher numbers of authentic-iPSCs following Vc treatment may in part be due to Vc-mediated transformation of partially reprogrammed pre-iPSCs into fully reprogrammed iPSCs (111). Furthermore, Stadtfeld et al 113,114 demonstrated that Vc treatment substantially improved the quality of iPSCs, reviving full developmental potential and unaltered genomic status (112). Generally, OSKM-transduced miPSCs bear altered epigenetic signatures at the imprinted Dlk1-Dio3 gene locus which modulates their ability to generate iPSC-derived adult mice through tetraploid complementation.…”
Section: Nutritional Supplements For Pluripotency Reprogrammingmentioning
confidence: 99%
See 1 more Smart Citation
“…In line with these findings, hiPSCs also seem to form teratomas faster and with higher aggressiveness than hESCs, irrespective of the site of administration or engraftment . Two new studies have observed that mitigation of oxidative stress during reprogramming and early passaging by using antioxidant supplements in the growth media was able to reduce genome instability in hiPSCs .…”
Section: Genetic Instability In Ipscsmentioning
confidence: 62%